Design of a terrain surface visualization program using algebra-algorithmic tools - Doroshenko, А.Yu.; Kushnirenko, R.V.; Yatsenko, O.A. (PROBLEMS IN PROGRAMMING, 2019)
One of the important challenges in meteorological forecasting is a computer visualization of prognosis data, in particular, three-dimensional modeling of terrain surface relief. One of the most popular software tools for developing data visualization applications is OpenGL, a cross-language, cross-platform application programming interface for rendering two-dimensional and three-dimensional vector graphics. Data visualization is a fairly complex task, therefore it is necessary to develop special tools intended for automated generation of source code for such tasks. The paper deals with the further development of previously developed algebra-algorithmic tools in the direction of automated design and synthesis of OpenGL programs. Automated construction of programs is implemented using a high-level language based on Glushkov’s system of algorithmic algebra. The approach is illustrated on designing a terrain surface relief visualization program for weather forecasting task.